The Relationship between mother's knowledge offood nutrition of Stunting in Toddlers in Singali Village, Hutaimbaru District, Padangsidimpuan City - endang, tapi (Universitas Aufa Royhan, 2021)
The most important phase in the growth and development of children during infancy and toddlerhood, because this is the most important period for parents to build the basis for child development. The type of research used in this study is a quantitative study using a cross sectional study approach with the aim of knowing the relationship of Mother's Food Knowledge about Food Nutrition of stunting under five in Singali village, Hutaimbaru district, Padangsidimpuan city, which was observed in the same time period. The time of the study was carried out from January to Mei 2021. The results of the analysis test on Mother's Food Knowledge about Food Nutrition in stunting prevention, obtained the value of person chi-square is 1.149 with a significance level of 5% = 0.050, df = 2, chi-square table value = 5.99148, it can be concluded that mother's knowledge has an influence on prevention stunting in toddlers in Singali Village, Padangsidimpuan Hutaimbaru District.